Evaluation of Northern Hemisphere surface wind speed and wind power density in multiple reanalysis datasets. (1st June 2020) - Miao, Haozeyu; Dong, Danhong; Huang, Gang; Hu, Kaiming; Tian, Qun; Gong, Yuanfa
Abstract: Reanalysis products have become more and more popular for wind energy scientific community to analyze the wind speed variability and get long-term wind power estimations. The present study evaluates the biases of near-surface wind speed and wind power density in four of the most reputable reanalysis datasets, which include ERA-Interim, JRA-55, CFS and MERRA-2. The results indicate that the abilities of reanalysis products to reproduce the variabilities of wind speeds are different in different regions. JRA-55 and CFS offer the best estimates of annual and seasonal variabilities of surface wind speeds over the Northern Hemisphere. In detail, JRA-55 is the best to reproduce surface wind speeds in Asia, CFS has the best performance in Europe, and MERRA-2 just can reproduce the central part of North America. All the four datasets show decreasing tendencies in surface winds over the Northern Hemisphere during 1980–2016, although the trends are largely diverse among them. The most significant disagreements of wind speed trends are encountered between JRA-55 and MERRA-2, which are likely related to the different methodologies from the lowest model level that reanalyses use. The main drivers of wind speed trends are the changes of large-scale circulation, urbanization, and aerosol emissions. Highlights: Comparison of multiple datasets over the Northern Hemisphere in the period 1980–2016. Different descriptive abilities for these datasets in different regions. JRA-55 and CFS reproduce wind speeds best in Asia and Europe, respectively. All datasets show decreasing trends of wind speeds with largely diverse among them. Trend disagreements from different methodologies at the lowest model level.